CURRICULA OF CIVIL EDUCATION AND CITIZENS OF THE FUTURE - Mimoza Carka; Lindita Lutaj (European Scientific Journal, ESJ, 2015)
Based on the fact that school, especially in obligatory system of education aims to make every single pupil successful one, it belongs to it to embody some life imperatives for the future of the country. In this context a special place is possessed from democratic civil education of pupils, where an essential role is played from curricula of civil education, in pupil’s preparation as worthy citizens of the future. The role and contribution of them in preparation of future citizens of this country, who will contribute for fundamental establishing of the society and knowledge, is not replaceable. In this study are reflected data from the review of modern literature and surveys or questionnaires done in 9 year school “Koto Hoxhi”, Gjirokastër (nr. 145, 75 males and 70 females), and in 9 year school “Qamil Gjuzi”, Elbasan (Nr.145, 70 males 75 females). The sample was chosen in a random way in both schools that have been part of the study. Education for democratic citizenship requires open curricula in order to include active pupils to analyze social policies. Related to this issue is important that existent teachers out of this profile need to be trained professionally in teaching issues of civil education subject, through individual and institutional qualifications. Internal and external assessments of education institutions, aim to assess not only the scientific level of pupils, but also their skills, as future citizens. Our society has had deep changes and also theoretical concepts and practical implementations of the citizenship where roles of teacher and pupils competences have changed especially toward the integrated teaching of knowledge.